Freezing effects and objects - LOHNDAL, TERJE (Journal of linguistics, 2011)
This paper is an investigation of freezing effects, that is, cases where an element (e.g. an object or a subject, or an element within it) is unable to move from a certain structural position. An account of the most prominent properties of freezing in Norwegian is followed by a comparative study of primarily English and Norwegian indirect objects, with important consequences for the general approach to indirect objects. Although recent analyses capture central properties of indirect objects, they fall short of accounting for freezing properties, seen here in terms of agreement properties, most notably Case agreement. It is shown that both subjects and indirect objects disallow sub-extraction in both English and Norwegian; however, unlike English, Norwegian allows the indirect object to Á-bar move. This relates to the question of whether Case is structural or inherent. As such, this paper offers a new argument in favor of Case as a central ingredient in deriving freezing effects.